Pain management for the neurosurgical patient in spinal procedures: overview of historic and new modalities - Ashley M. Carter; Samantha Yost; Jessica Tobin; Simran Phuyal; Brandon Lucke-Wold (Exploration of Drug Science)
The potent pain-relieving properties of opioids come at a steep price. Their addictive nature and side effects raise critical concerns in managing pain after surgical spine procedures. Postoperatively, spinal surgeries often accompany acute intense pain, which presents a significant challenge in optimal recovery. This paper reviews the historical approach to pain management in spine surgeries and expands on the use of alternatives and novel agents with reduced addictive potential. Additionally showcasing individualized multimodal strategies for postoperative pain management beyond pharmacological approaches such as cognitive behavioral therapy (CBT), physical therapy, and transcutaneous electrical nerve stimulation (TENS). Given the global opioid addiction crisis, there is a growing need for a fundamental shift towards safer and effective alternatives. Transitioning beyond opioid-centric practices in spinal surgery can optimize pain relief while improving patient outcomes and minimizing risk.